THE VALUE OF UNITY IN NUTUK BEHAM CEREMONY IN KUTAI ADAT LAWAS COMMUNITY AT KEDANG IPIL VILLAGE - Janah, Ulum; Adam, Muhammad (Proceedings of English Linguistics and Literature, 2020)
Culture is one form of stabilization of a society. This is because culture brings noble values that continuously give knowledge to society in maintaining relationshipetween human with God, human with fellow human, human with nature, and human with the era development. Culture becomes functional in bringing society in unity. One of the cultures that have the function to lift the value of unity is the Nutuk Beham ceremony performed by Adat Lawas society at Kedang Ipil village, Kota Bangun. This research employs ideational pproach, where Nutuk Beham has patterns to act and to result a form of public action which is unity in its tribal society. This aspect is inseparable from the systems of knowledge and symbols that are commonly shared by Kedang Ipil village society. Qualitative methodology is used in this research with ideational pproach by employing the systems of knowledge of Kedang Ipil society and the interpretation of the symbols appear in the ceremony. The result of the interpretation is manifested in the form of value of unity and the function of Nutuk Beham ceremony